Pain syndrome in rheumatology - N. A. Shostak; N. G. Pravdyuk; A. A. Klimenko; A. A. Kondrashov (Медицинский совет, 2013)
The article tells about types of pain at such rheumatic diseases as osteoarthritis and gout. The most common and socially significant clinical types of osteoarthritis, gonarthrosis and coxarthrosis, and approaches to treatment of pain in these pathologies, are described. The process of treatment of gout patient is described in detail. The main approaches to medicine-based treatment of pain syndrome at rheumatic disease are highlighted.